AN ANALYSIS OF NARRATIVE TEXT MADE BY THE INDONESIAN STUDENTS ON INTERNATIONAL JUNIOR HIGH SCHOOL IN NORTH JAKARTA (RETAIN, 2016)
AN ANALYSIS OF NARRATIVE TEXT MADE BY THE INDONESIAN STUDENTS ON INTERNATIONAL JUNIOR HIGH SCHOOL IN NORTH JAKARTA Angen Yudho Kisworo English Education, Faculty of Languages and arts, State Univerity of Surabaya angenyudho@gmail.com Wiwiet Eva Savitri English Education, Faculty of Languages and arts, State Univerity of Surabaya wiwieteva@unesa.ac.id Abstrak Menulisnaratifadalahkeahlian yang harusdimilikiolehsemuasiswa Indonesia. Akan tetapi, halinisangatkomplekskarenaberhubungandengankomponenpenulisan, konten, danorganisasipenulisan. Sehubungandengankompleksitasnya,beberapapenelitiantelahmenganalisisproduktulisansiswadanmenemukanbahwaterdapatbeberapakesalahandidalamnya. Tetapi, penelitiantersebuttidakmencakupobjekpenelitian yang berbeda yang dapatmengembangkanpengetahuantentangobjekpenelitian. Olehkarenaitu, penelitianinimenjelaskantentangobjek yang berbedadimanaakanberhubungandengansiswa Indonesia yang belajar di sekolahinternasional. Penelitiankualitatifdigunakandanpenelitianinimenganalisis 10 siswadanmenilaikomponenpenulisanmereka. Hasilnyamenunjukkanbahwasiswa Indonesia memelikikemampuan yang baikdalampembendaharaan kata, penggunaanbahasa, danmekanik. Tetapi, merekatidakmemilikikemampuan yang cukupdalammembangunorganisasidanmembuatkontentulisan yang manahalinimempengaruhigayapenulisanmereka. Kata Kunci: Naratif, komponen penulisan, gaya penulisan Abstract Writing narrative is the skill that all Indonesian students should have. However, it is very complex because it deals with complex writing components, content and organization of the writing. Regarding to its complexity, some research has analyzed the students` writing product and found that there were some mistakes in it. However, the previous studies did not scope different object of the study, which could expand the understanding of the object. Therefore, this study explains different object of study, which deals with Indonesian students who learn in international school. Qualitative research was used for this study, and it analyzed 10 Indonesian students and scored their writing components. The results showed that the Indonesian students had the good skills in vocabulary, language use and mechanics. Yet, they did not have adequate skill in arranging the organization and creating the content in which it influences their writing style. Keywords:Narrative, writing components, writing style